PENERAPAN PROBLEM BASED LEARNING DENGAN BRIDGING ANALOGY UNTUK MENINGKATKAN KEMAMPUAN PENALARAN SISWA: IMPLEMENTATION OF PROBLEM BASED LEARNING WITH BRIDGING ANALOGY TO IMPROVE STUDENTS' REASONING ABILITY - Hariyanti, Firda; Nisa, Ulfatun; Hidayah Al Mubarokah, Nurul; Lina Safitri, Nur (PANDU : Jurnal Pendidikan Anak dan Pendidikan Umum, 2023)
Students need to improve mathematical competence not just counting but the ability to reason, namely logical and critical thinking in problem solving. In addition, the demands of students today are related to the Pancasila profile students, one of which is critical reasoning. The learning process at school should facilitate students in improving their reasoning skills. However, PISA 2022 which emphasizes student assessment of student reasoning reports the results are still below the International average. Therefore, it is important to apply a learning model that can improve student reasoning. This study aims to provide an overview of the application of the Problem Based Learning (PBL) learning model with the Bridging Analogy approach to improve student reasoning. The description of teacher activities, student activities, mathematical reasoning test results and student responses become a reference in seeing the effectiveness of the learning model applied to improve student reasoning. This research method is descriptive qualitative. Based on the results of the study, it can be concluded that the implementation of teacher and student activities in the application of the PBL model with the Bridging analogy approach is in the good category. Students' mathematical reasoning increased after the application of the problem-based learning model with a bridging analogy approach, both in subjects who had high, medium, and low initial abilities on the material of function derivatives.